Concomitant drugs with low risks of drug–drug interactions for use in oncology clinical trials. Issue 2 (May 2015) - Ranchon, Florence; Vial, Thierry; Rioufol, Catherine; Hénin, Emilie; Falandry, Claire; Freyer, Gilles; Trillet-Lenoir, Véronique; Le Tourneau, Christophe; You, Benoit
Highlights Drug–drug interactions (DDIs) must be avoided in patients enrolled in oncology clinical trials, as they can compromise patient safety and trial outcomes. Lists of cautioned or prohibited concomitant drugs, commonly included in trial protocol appendixes, are not helpful when clinicians are confronted by the need to prescribe concomitant medications with minimal risks of DDIs. The development of an inventory of preferred drugs less prone to DDIs related to CYP450; membrane transporter; or QT prolongation may complement prohibited/cautioned medication lists. We compiled a list of preferred drugs with minimal risks of drug–drug interactions for treatment of symptoms or comorbidities frequently encountered by cancer patients. It could be provided within trial protocol as a practical guidance to clinicians who have to replace a medication, or to manage patients' symptoms with the best non-prohibited concomitant drugs in terms of DDI prevention.